Girls, Autobiography, Media Gender and Self-Mediation in Digital Economies - Maguire, Emma (Palgrave Studies in Life Writing, 2018)
This book investigates how girls' automedial selves are constituted and consumed as literary or media products in a digital landscape dominated by intimate, though quite public, modes of self-disclosure and pervaded by broader practices of self-branding. In thinking about how girlhood as a potentially vulnerable subject position circulates as a commodity, Girls, Autobiography, Media argues that by using digital technologies to write themselves into culture, girls and young women are staking a claim on public space and asserting the right to create and distribute their own representations of girlhood. Their texts-in the form of blogs, vlogs, photo-sharing platforms, online diaries and fangirl identities-show how they navigate the sometimes hostile conditions of online spaces in order to become narrators of their own lives and stories. By examining case studies across different digital forms of self-presentation by girls and young women, this book considers how mediation and autobiographical practices are deeply interlinked, and it highlights the significant contribution girls and young women have made to contemporary digital forms of life narrative.